EVALUASI PELAKSANAAN PERIZINAN HUTAN TANAMAN INDUSTRI (HTI) DI KABUPATEN PELALAWAN(STUDI KASUS PT. RAPP TAHUN 2013-2015) - Hasby Rabdi; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Regulations permit Plantation Forestry in many abused by some companies in Pelalawan them is PT. RAPP causing a forest fire and haze in Riau Province. Haze is the worst in 2015 which went on for three months. This is due to permit violations of Industrial Plantation Forest (HTI) by PT. RAPP in Pelalawan Riau Province. Therefore the violations permission Industrial Plantation Forest (HTI) and the consequences are detrimental to society then the purpose of the policy is not tercapai.Tujuan forest productivity and production of this study is to evaluate and determine what factors affecting Implementation Evaluation and Licensing of Industrial Plantation Forest ( HTI) in Pelalawan (Case Study PT.RAPP Year 2013-2015) Researchers used the theory of William N Dunn stating that a policy evaluation criteria of effectiveness, efficiency, adequacy, grading, responsiveness and permanence. This study used descriptive qualitative method, data collection through observation and interviews in which the parties involved in this study as an informant. The evaluation results indicate that the implementation of the licensing Licensing of Industrial Plantation Forest (HTI) in Pelalawan (Case Study PT. RAPP Year 2013-2015) as seen from the sixth indicator has not done well in which the purpose of the policy is yet to be achieved. Then this policy still had a negative impact or a negative impact on society around such problems occurred, namely making public land belonging to the conversion of industrial plantations and forest fires which occurred during the opening of new land, causing smog that harm society Riau Province. Factors - factors that affect Implementation Evaluation and Licensing of Industrial Plantation Forest (HTI) in Pelalawan (Case Study PT.RAPP Year 2013-2015) is the Communication and Coordination. Keywords :Implementation Evaluation and Licensing of Industrial Plantation Forest (HTI)